2009
DOI: 10.1177/0734904109346396
|View full text |Cite
|
Sign up to set email alerts
|

The Modeling of Heat Transfer across Intumescent Polymer Coatings

Abstract: The use of mathematical models to predict the thermal resistance of polymer-based, intumescent coatings are reviewed and their limitations are discussed. A mathematical model is derived to describe the developing temperature profile across an intumescent coating when exposed to a radiant heat source. The model includes the effects of: the endothermic and exothermic reactions; convective heat transfer as degradation gases are transported through the coating; radiation heat transfer across the developing porous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…Non-charring polymers, on the other hand, are significantly flammable and generally transform into gaseous volatile species almost completely during pyrolysis reactions, thus leaving no or little residue [2]. Intumescent polymers, in contrast, are capable of forming substantial amounts of carbonaceous residue, which in turn protects the surface of polymers that are being exposed to an external heat flux [3]. The carbon-rich char residue, initially formed, can undergo rapid expansion primarily owing to the production of non-combustible gaseous species emanating from the decomposing spumific agent within the intumescent formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Non-charring polymers, on the other hand, are significantly flammable and generally transform into gaseous volatile species almost completely during pyrolysis reactions, thus leaving no or little residue [2]. Intumescent polymers, in contrast, are capable of forming substantial amounts of carbonaceous residue, which in turn protects the surface of polymers that are being exposed to an external heat flux [3]. The carbon-rich char residue, initially formed, can undergo rapid expansion primarily owing to the production of non-combustible gaseous species emanating from the decomposing spumific agent within the intumescent formulation.…”
Section: Introductionmentioning
confidence: 99%
“…Nano fillers have superior surface-to-volume ratio but they are extremely difficult to disperse uniformly [10]. Thus, the weight percentage of nano fillers plays an important role in enhancing the intumescent fire retardant coating.…”
Section: Elemental Analysis Of Charmentioning
confidence: 99%
“…Existing intumescent fire retardant coatings reported that the char layer would damage easily by the turbulence during flame spread. The residual weight of the coating is also low as it is easily oxidized at high temperature [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have also been made to address the shortcomings of furnace testing on reactive coatings using cone calorimeters [11,12,13,14]. These studies used cone calorimeter tests to determine thermal properties of the intumescent coating under a range of constant incident heat fluxes.…”
Section: Motivationmentioning
confidence: 99%